2022
DOI: 10.17240/aibuefd.2022.22.74506-1003537
|View full text |Cite
|
Sign up to set email alerts
|

Pandemi Döneminde İlkokul Birinci Sınıf Öğrenci Velilerinin Uzaktan Eğitime Yönelik Görüşleri

Abstract: Bu çalışmada, ilkokul birinci sınıfa giden öğrenci velilerinin pandemi döneminde uzaktan eğitim süreci hakkındaki görüşlerinin belirlenmesi amaçlanmaktadır. Bu çalışmada, nitel araştırma yöntemlerinden durum çalışması deseni kullanılmıştır. Araştırma verileri, yarı yapılandırılmış görüşme formu aracılığıyla 9 anne, 7 baba olmak üzere toplam 16 ebeveynden toplanmıştır. Görüşme verileri, içerik analizi yöntemi kullanılarak analiz edilmiştir. Analiz sonucunda 4 kategori, 10 alt kategori ve 37 kod belirlenmiştir. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In the world that evaluates the distance education process from the eyes of parents (Ali, 2020;Alipio, 2020;Bozkurt et al, 2020;Daniela et al, 2021;Dong, Cao & Li, 2020;Garbe et al, 2020;Griffith, 2020;Khan, 2020;Arslan et al, 2021;Başaran et al, 2020;Bozkurt, 2020;Can, 2020;Çiçek et al, 2020;Aruğaslan et al, 2022;Gür & Filiz, 2022;Güvercin et al, 2022;Ayten & Ercan, 2022 ) various studies have been conducted. Aruğaslan et al (2022), in their study with primary school first grade parents found that parents took additional responsibilities to support their children, provide educational, psychological and technological support to their children, and experience technological problems. In addition, they found that students' communication with their friends and teachers decreased, teachers' interaction with parents increased, they thought that distance education would not replace face-to-face education and that it was an important system that could be used in situations where it was impossible to go to school.…”
Section: Literaturementioning
confidence: 99%
“…In the world that evaluates the distance education process from the eyes of parents (Ali, 2020;Alipio, 2020;Bozkurt et al, 2020;Daniela et al, 2021;Dong, Cao & Li, 2020;Garbe et al, 2020;Griffith, 2020;Khan, 2020;Arslan et al, 2021;Başaran et al, 2020;Bozkurt, 2020;Can, 2020;Çiçek et al, 2020;Aruğaslan et al, 2022;Gür & Filiz, 2022;Güvercin et al, 2022;Ayten & Ercan, 2022 ) various studies have been conducted. Aruğaslan et al (2022), in their study with primary school first grade parents found that parents took additional responsibilities to support their children, provide educational, psychological and technological support to their children, and experience technological problems. In addition, they found that students' communication with their friends and teachers decreased, teachers' interaction with parents increased, they thought that distance education would not replace face-to-face education and that it was an important system that could be used in situations where it was impossible to go to school.…”
Section: Literaturementioning
confidence: 99%